(3JaSjQ dZI TQYI GdESdGes - (3eLghds
(3ChdgG (B:s
(3gPG cJGH TQYI dZI GdESdGe GdMeO ddg EYdGe bGFO SGjhfG NdbdeYJgddYbhOYbOefJbOTPhQYbGFdeUGHjMs
(3BNQgG (B:s
(3TgGH Cgd cJGH MJi LU aSWGWLgQ Mjd MGaj CaVhGs
(3Hjf SWhQg JQLeI HGddZI GdaGQSjI, hgPG GdeNWhW JQLeI dHYV eaQOGJ cJGH TQYI GdESdGe (B( (3ddEeGe RGOg GdMfaj J(B573(3g`(B) (3Edi GddZI GdJQcjIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GddZIs